1982
DOI: 10.2307/3429427
|View full text |Cite
|
Sign up to set email alerts
|

Organic N-Chloramines: Chemistry and Toxicology

Abstract: The stability of aqueous solutions of organic N-chloramines, suspected of contaminating chlorinated water, has been studied. Two factors influence the decomposition of solutions of N-chloropiperidine and N-chlorodiethylamine: a spontaneous decomposition and photodecomposition. Since solutions of these compounds are relatively long-lived, a need for an analytical method for their identification is discussed. A new method is described which involves reaction of organic N-chloramines with arenesulfinic acid salts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 4 publications
2
20
0
Order By: Relevance
“…Most of the degradation rate constants determined in this work were in agreement with previously reported values (Armesto et al 1996, Hand et al 1983, with the exception of Nchloroproline (Hand et al 1983), N-chlorodimethylamine and N-chlorodiethylamine (Scully and Bempong 1982), where the rate constants were about one order of magnitude higher in the current study, compared to the respective previous studies. We note that the relative standard deviation of rate constants that we determined for N-chloroproline, Nchlorodimethylamine and N-chlorodiethylamine, being less than 15% over 4 replicate experiments (Tables 2), indicated good experimental repeatability.…”
Section: Kinetic Study Of the Degradation Of Organic Chloraminessupporting
confidence: 92%
See 2 more Smart Citations
“…Most of the degradation rate constants determined in this work were in agreement with previously reported values (Armesto et al 1996, Hand et al 1983, with the exception of Nchloroproline (Hand et al 1983), N-chlorodimethylamine and N-chlorodiethylamine (Scully and Bempong 1982), where the rate constants were about one order of magnitude higher in the current study, compared to the respective previous studies. We note that the relative standard deviation of rate constants that we determined for N-chloroproline, Nchlorodimethylamine and N-chlorodiethylamine, being less than 15% over 4 replicate experiments (Tables 2), indicated good experimental repeatability.…”
Section: Kinetic Study Of the Degradation Of Organic Chloraminessupporting
confidence: 92%
“…In this study, the pH was about 8 and unbuffered, which is higher than the pH used in previous studies. The degradation rate constant for N-chloroproline was previously determined at pH 6.85 using 0.01 M phosphate buffer (Hand et al 1983), while the degradation rates constants for N-chlorodimethylamine and N-chlorodiethylamine were previously determined at pH 7 (Scully and Bempong 1982). The results suggested that higher pH destabilised the chlorine to nitrogen bond in organic monochloramines formed from secondary amines resulting in faster degradation of organic monochloramines.…”
Section: Kinetic Study Of the Degradation Of Organic Chloraminesmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid reaction of the test chemicals with amines and other compounds in the culture medium, cells were exposed in a simple salts solution, and the S9‐metabolic activation system was not included in this study. Previous studies have shown that several organic N ‐chloramines were mutagenic in bacteria without a requirement of metabolic activation [Scully and Bempong,1982; Süssmuth,1982; Nakamura et al,1993]. On the day of experiment, organic N ‐chloramines were freshly produced using the condition selected from experiments described previously.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that alterations of these parameters are common properties found in carcinogens. A number of in vitro studies have demonstrated mutagenicity of several organic N ‐chloramines in bacteria, without the need for metabolic activation [Scully and Bempong,1982; Süssmuth,1982; Thomas et al,1987; Nakamura et al,1993], as well as cytostatic or cytotoxic effects in Chinese hamster ovary cells [Bempong and Scully,1980]. However, currently, there have been no in vivo toxicity studies on organic N ‐chloramines, and, without a training set, the QSTR program used by Bull et al [2006] was unable to predict the carcinogenic risks associated with compounds in this group.…”
Section: Introductionmentioning
confidence: 99%